Didactic Design Implementation on Algorithms and Programming to Improve Students’ High School Computational Thinking - Hassan Hidayatullah; Eka Fitrajaya Rahman; Harsa Wara Prabawa (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2026)
This research is motivated by the urgency of mastering 21st-century skills, particularly Computational Thinking (CT) in Informatics learning, and the prevalence of learning obstacles experienced by students. This study aims to develop a valid and effective didactical design to overcome students' learning obstacles and enhance their CT skills. The research method used is Didactical Design Research (DDR), which encompasses three stages: prospective analysis, metapedidactical analysis, and retrospective analysis. The research subjects involved Senior High School students in SMAN 9 Bandung. Data collection instruments included CT ability tests, interview guides, and classroom observations to identify ontogenic, didactical, and epistemological obstacles. The results indicate that the developed Hypothetical Didactical Design (DDH) proved effective, with a success rate of approximately 77.14% in overcoming students' learning obstacles. The implementation of this design also positively impacted the improvement of CT pillars, including decomposition, pattern recognition, abstraction, and algorithmic thinking. Furthermore, through retrospective analysis, the Empirical Didactical Design (DDE) was formulated to refine the design and address shortcomings identified in the DDH. This study recommends the application of learning obstacles-based didactical design as a responsive alternative strategy for Informatics learning.